AKTIVITAS ANTI HEPATITIS C DARI FRAKSI SPONS Homaxinella tanitai DAN IDENTIFIKASI SENYAWA PADA FRAKSI AKTIF - IRSYAD ABDILLAH, 051311133109 (2017)
Marine sponge has been reported as the source of many metabolites with various pharmacological activity, including antiviral activity. Previous study reported that ethyl acetate extract of Homaxinella tanitai sponge had antiviral activity againts hepatitis C virus with IC50 value of 27,12 μg/mL. The purpose of the current study is to evaluated antiviral activity of the fractions of ethyl acetat extract of H. tanitai as well as to investigate the secondary metabolites in the active fraction obtained. Fractionation of the ethyl acetate extract of H. tanitai was performed on Sepacore® flash chromatography. The in vitro antiviral activity test was conducted by using indirect immunoenzyme staining on fractions obtained at concentration 100 ppm against JFH1 virus and Huh7it cell. The results showed that the % inhibition of fractions 4, 5, 6, and 7 were 88,5±3,1%, 96,2±2,7%, 68,4±10,2%, and 53,0±9,8%, respectively. The compound analysis was conducted by using proton Nuclear Magnetic Resonance (NMR), Thin Layer Chromatography (TLC) with vanillin stain visualization and Gas Chromatography Mass Spectroscopy (GCMS). The result of 1HNMR analysis indicated that the major compound in fractions 4 and 5 were fatty acid, which was further confirmed by TLC. The GCMS analysis successfully identified eight fatty acids namely tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, 8,11- octadecadienoic acid, 9, 12, 15-octadecatrienoic acid, octadecanoic acid, and eicosanoic acid. These findings suggested that fatty acid metabolites may be responsible for the antiviral activity of the fraction.